MODERN FINTECH DIRECTIONS IN THE BANKING SECTOR - CHAIKOVSKYI, Yaroslav; KOVALCHUK, Yaroslava (Scientific journal «World of Finance», 2020)
Introduction. One of the factors behind structural changes in Ukraine's financial market is the increasing use of the Internet and mobile devices to provide financial services. It can be seen now that radical changes in technology have affected not only the information sphere but also the economic sphere. The current technological revolution has also had a significant impact, including on the banking sector's infrastructure, which is associated with increased automation in bank operations and greater customer focus. For the most part, such transformations in the industry are associated with the need to reduce costs, improve the security of financial transactions, and ensure that the service industry is responsive to an ever-evolving society.The purpose is to determine trends directions of research of new financial technologies in the banking industry.Methods. The theoretical and methodological basis of the article is the scientific works of domestic and foreign scientists and specialists in the theory of banking innovation and financial technologies. In the course of the research, such general scientific methods of cognition were used as: theoretical generalization, comparison, and systematization (in the study of the essence of the concepts of “financial technology”, “fintech”, “artificial intelligence”, “open banking”, “blockchain”; definition of types of financial technologies); observation (during the study of implemented fintech in banking institutions); graphical method – for visual presentation of analysis results.Results. The essence of the concept of “financial technology” is disclosed in the article. Modern fintech trends in Ukraine and in the world are analyzed. Also, presents the most successful examples of the use of financial technologies in the banking sector in recent years. In addition, a number of areas for future research in the field of financial technology, which are currently very promising in the banking sector and could be launched in Ukraine and worldwide are offered.Conclusions. Given the significant interbank competition, the problem of developing financial technologies in the provision of financial services by banking institutions has become particularly urgent. In addition, the improvement of financial technologies is not a simple matter and should be multifaceted in order to ensure the efficiency and expected performance of banks. Therefore, it is necessary to improve not only financial technologies, financial services and products, but also ways of providing them to clients of banking institutions, communication of bank employees with clients, advertising, promotion of modern financial technologies, etc. Financing, all kinds of consulting services and payments can all be considered as one of the most promising areas for future research in financial technology.